2020
DOI: 10.3390/f11030345
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of the Fine Roots of Two Broadleaved Tree Species from the Temperate Caspian Hyrcanian Ecoregion

Abstract: In view of the important role played by roots against shallow landslides, root tensile force was evaluated for two widespread temperate tree species within the Caspian Hyrcanian Ecoregion, i.e., Fagus orientalis L. and Carpinus betulus L. Fine roots (0.02 to 7.99 mm) were collected from five trees of each species at three different elevations (400, 950, and 1350 m a.s.l.), across three diameter at breast height (DBH) classes (small = 7.5–32.5 cm, medium = 32.6–57.5 cm, and large =57.6–82.5 cm), and at two slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…Such condition is related to botanic, climatic and environmental factors (Hales et al, 2009;Hales & Miniat, 2017) i.e. plant species, stand origin and structure and physical and chemical properties of soil (Bischetti et al, 2005;Deljouei et al, 2020). It has been observed that root reinforcement is systematically dependent on various environmental conditions such as soil moisture (Fan and Su, 2009;Hales et al, 2009), plant functional types (Moresi et al, 2019, Hales, 2018, and plant age (Dazio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such condition is related to botanic, climatic and environmental factors (Hales et al, 2009;Hales & Miniat, 2017) i.e. plant species, stand origin and structure and physical and chemical properties of soil (Bischetti et al, 2005;Deljouei et al, 2020). It has been observed that root reinforcement is systematically dependent on various environmental conditions such as soil moisture (Fan and Su, 2009;Hales et al, 2009), plant functional types (Moresi et al, 2019, Hales, 2018, and plant age (Dazio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…C.A. Mey (Persian Ironwood) [8]. The district has 12.2 km of unpaved permanent main forest road (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…Yet, despite substantial advances in the field of biogeomorphology during last two decades [38,42,[58][59][60]63,274], important knowledge gaps regarding the relev biophysical interactions remain [39,45,62,275]. For instance, the magnitude and rela importance of often competing biotic effects, as well as their variability (e.g., relate plant age or species), are still relatively poorly explored [76,[276][277][278]. Equally importan the dynamic co-adjustments between vegetation, flow, and sediment cannot be understood and quantified without a better insight into the physiological tolerance responses of plants to hydraulic and geomorphic stress and disturbances [279]; th questions have mostly been explored in detail in a few common, well-studied spe However, while past research provides some important insights into the roles that vegetation-connectivity linkages may play in regulating geomorphic responses to environmental change, further work is warranted.…”
Section: Vegetation-geomorphic Connectivity Linkages: Some Challenges To Understanding Fluvial Behavior In Mountain Landscape Systemsmentioning
confidence: 99%